The proteomic revolution - Gold, Larry (Henry Stewart Talks, 2012)
The proteomic revolution, Proteomics is the best measure of phenotype (biomarkers), Slow Off-rate Modified Aptamers (SOMAmers) are breakthrough protein binding reagents, SOMAmers are multiplexed to perform SOMAscan assay, which measures >1000 proteins in small sample volumes using DNA measurement tools to identify and quantify proteins bound by SOMAmers, Applications of SOMAscan to date include finding valid protein biomarkers for lung cancer, cardiovascular risk, pre-term birth, pancreatic cancer, mesothelioma, and many other diseases and conditions, Ability to do comprehensive longitudinal proteomics studies will revolutionize medicine
Updated at 2022/05/29